Adverse Childhood Experiences and Associated Mental Distress and Suicide Risk: Results From the Zambia Violence Against Children Survey. Issue 21 (November 2022) - Lee, NaeHyung; Massetti, Greta M.; Perry, Elizabeth W.; Self-Brown, Shannon
Purpose: Adverse childhood experiences (ACEs) are a global public health concern. Little research exists on the prevalence and health consequences of ACEs in Zambia. The current study examined associations between individual and cumulative ACEs, mental distress, and suicide risk among Zambian youth.Methods: Data from Zambia Violence Against Children and Youth Survey were used (18-24 years old, n=1034). Bivariate and adjusted logistic models were performed with independent variables (i.e., experienced physical violence (PV), sexual violence (SV), and emotional violence (EV); witnessed intimate partner violence (IPV) and community violence (CV); orphan status; cumulative ACE exposure) and dependent variables (i.e., mental distress and suicide risk). Adjusted models controlled for demographic and social characteristics.Results: 76.8% of Zambian youth experienced one or more ACEs, and more than 30% witnessed CV (38.4%) or IPV (30.2%), or experienced PV (35.1%), prior to age 18. 27.5% were orphans, and less than 20% experienced EV (17.3%) or SV (15.4%) in childhood. 42.4% experienced mental distress in the past 30 days, and 12.5% reported lifetime suicidal thoughts or suicide attempts. PV, EV, cumulative ACE exposure, older age, being single, and stronger friendships were significantly related to experiencing mental distress. Cumulative ACEs exposure was associated with significantly higher suicide risk.Conclusions: Preventing ACEs can reduce mental distress and suicide risk among Zambian youth. Youth with cumulative ACE exposure can be prioritized for mental health intervention. More research is warranted to investigate the broad-based prevention of ACEs, especially PV and EV, and protective factors that can promote resilience among youth who have experienced ACEs.